Perbedaan status gizi antara perokok dan bukan perokok pada mahasiswa Politeknik Kesehatan Kemenkes Aceh - Indra Kurniawan; T. Khairul Fadjri; Agus Hendra Al Rahmad (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Smoking habits can have a negative impact on smokers and those around them. Smokers tend to have a lower body mass index (BMI) than nonsmokers in various populations. The average cigarette smoked per day per person in Indonesia is 12.3 cigarettes (equivalent to one pack). Smokers generally have a lower body weight than non-smokers.Objectives: This study aims to determine differences in nutritional status or body mass index (BMI) between smokers and non-smokers.Methods: The study used cross-sectional, with a sample of 66 students. The research was conducted at the Health Polytechnic of the Ministry of Health in 2019. Data collection was carried out by direct interviews using questionnaires, as well as anthropometric measurements (weight and height) to assess nutritional status. Data processing was carried out by categorizing smokers and non-smokers, and nutritional status using the z-score of BMI. Data analysis used Independent T-test at 95% CI.Results: The results have reported that students' smoking habits are carried out outside the home (81.8%) by smoking between 3-6 cigarettes/day. Student nutritional status (BMI) in smokers 21.33 kg/m2 and non-smokers 21.86 kg/m2. Statistically, there was no difference (p= 0.600) between the nutritional status of smoking students and non-smoking students at the Health Polytechnic of Aceh, Ministry of Health (p > 0.05). Conclusion: There is no difference in nutritional status (BMI) between smoking students and non-smoking students at the Health Polytechnic of Aceh, Ministry of Health.